Strategi Implementasi Projek Penguatan Profil Pelajar Pancasila Terhadap Prestasi Belajar Siswa SDN Ibu Dewi 1 Kabupaten Cianjur - H. Soro, Suharyanto; Suherman, Maman; Mulyadi, Budi; Setiani, Erna Erawati; Silviana, Karisma (LP. Ma'arif Janggan Magetan, 2024)
This study is rooted in the concept of the Pancasila Student Profile initiated by the Ministry of Education and Culture. The Pancasila Student Profile describes the ideal figure of an Indonesian education graduate who has six dimensions, namely: Faithful, devoted to God Almighty, and noble character. This study aims to exploit the implementation of the Pancasila Student Profile Strengthening Project (P5) at SDN IBU DEWI 1 to instill character values ​​in elementary school students. This study uses a case study approach with a qualitative research paradigm. Data were collected through observation, interviews, documentation, and literature studies. The results of the study indicate that: (1) the activity of displaying student learning outcomes is very effective in instilling Pancasila values ​​such as diversity, mutual cooperation, and independence; (2) The involvement of teachers, parents, and the school community is very important in making this program a success. The P5 program is able to improve students' cognitive, affective, psychomotor and social skills; (3) Evaluation of the implementation of the program indicates that this project-based learning method has a significant positive impact on the development of elementary school students.